2019
DOI: 10.1002/wer.1052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solids residence time on dynamic responses in chemical P removal

Abstract: The impact of solids residence time (SRT) on the dynamics of phosphorus (P) removal by hydrous ferric oxide (HFO) floc was characterized through experimental and modeling studies. Three abiotic process conditions were considered in systems operated over a range of SRTs (~3 to 27 days): uptake in sequencing batch reactors (SBRs) under (a) constant and (b) dynamic P loading conditions, and (c) uptake in batch sorption tests with preformed HFO solids. P removal under all conditions was characterized by an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The produced Fe 3+ from the oxidation of Fe 2+ undergoes several hydrolysis processes forming various ferric species such as FeOH 2+ , Fe (OH) 2 + , Fe (OH) 3(aq) , and Fe (OH) 4 − (Hauduc et al, 2015). Although iron hydrolysis has been investigated widely, there is no general consensus on the exact composition of ferric hydrolysis species; however, several studies have demonstrated that Fe(OH) 3(aq) is the dominant hydrolysis species (Pham et al, 2006) and considered to be the main precursor for the formation of HFO precipitants, which for simplicity can be described as Fe(OH) 3(s) (Conidi et al, 2019; Smith et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The produced Fe 3+ from the oxidation of Fe 2+ undergoes several hydrolysis processes forming various ferric species such as FeOH 2+ , Fe (OH) 2 + , Fe (OH) 3(aq) , and Fe (OH) 4 − (Hauduc et al, 2015). Although iron hydrolysis has been investigated widely, there is no general consensus on the exact composition of ferric hydrolysis species; however, several studies have demonstrated that Fe(OH) 3(aq) is the dominant hydrolysis species (Pham et al, 2006) and considered to be the main precursor for the formation of HFO precipitants, which for simplicity can be described as Fe(OH) 3(s) (Conidi et al, 2019; Smith et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…When the flow rate was 1.5, 3, and 4.5 mL/min, the adsorption penetration time decreased from 120 min to 70 min and 50 min; and the adsorption saturation time decreased from 320 min to 230 min and 130 min. The increase in influent flow rate reduces the contact time between Ph and MBCQ, resulting in an insufficient time for Ph to undergo membrane diffusion and intraparticle diffusion [36]. The MBCQ utilization rate decreased with the increase of the mass transfer zone length.…”
Section: Effect Of Flow Rate On the Breakthrough Curvementioning
confidence: 99%
“…The use cycle and treatment effect of the adsorption column were affected by the flow rate. How to control the flow rate of adsorbent to fully exploit the role of the adsorbent under the premise of ensuring optimal water yield is an important parameter to consider in the practical application of an adsorption column [36].…”
Section: Effect Of Flow Rate On the Breakthrough Curvementioning
confidence: 99%
See 1 more Smart Citation
“…The model matched the field measurements, with the exception of the vented HPO headspace gas oxygen content. Conidi, Parker, and Smith (2019) developed an abiotic ANNUAL LITERATURE REVIEW kinetic model of P adsorption and for simulating the time-varying dynamics of P removal through iron addition. Burger et al (2019) calibrated a plant-wide BioWin model based on 6 months of data and used it to estimate approximately 20% energy reduction from implementing ammonia-based aeration control (ABAC) and another 10% savings from converting to fine pore diffusers in the postanaerobic low-DO aerobic digester.…”
Section: Modelingmentioning
confidence: 99%